2021
DOI: 10.1073/pnas.2018234118
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hydrophobic protein patches to inform protein interaction interfaces

Abstract: Interactions between proteins lie at the heart of numerous biological processes and are essential for the proper functioning of the cell. Although the importance of hydrophobic residues in driving protein interactions is universally accepted, a characterization of protein hydrophobicity, which informs its interactions, has remained elusive. The challenge lies in capturing the collective response of the protein hydration waters to the nanoscale chemical and topographical protein patterns, which determine protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 72 publications
6
85
0
Order By: Relevance
“…To identify a relationship between Δ ins and quantitative metrics of a membrane's interfacial hydrophobicity, we have considered variations due to lipid headgroup, which modulate interfacial hydrophobicity through changes in mem−solv , separately from variations due to tail chemistry and membrane phase, which tune interfacial hydrophobicity through changes in ¯ defect . More sophisticated and precise measures of a membrane's interfacial hydrophobicity, such as those developed for protein surfaces (77)(78)(79)(80), may abrogate the need to consider contributions from headgroups separately from lipid tails and membrane phase. However, the two simple measures that we identify, mem−solv and ¯ defect , reasonably explain variations in Δ ins for different membranes relative to the errors in calculated values of Δ ins .…”
Section: Insertion Barrier Depends On a Membrane's Interfacial Hydrop...mentioning
confidence: 99%
“…To identify a relationship between Δ ins and quantitative metrics of a membrane's interfacial hydrophobicity, we have considered variations due to lipid headgroup, which modulate interfacial hydrophobicity through changes in mem−solv , separately from variations due to tail chemistry and membrane phase, which tune interfacial hydrophobicity through changes in ¯ defect . More sophisticated and precise measures of a membrane's interfacial hydrophobicity, such as those developed for protein surfaces (77)(78)(79)(80), may abrogate the need to consider contributions from headgroups separately from lipid tails and membrane phase. However, the two simple measures that we identify, mem−solv and ¯ defect , reasonably explain variations in Δ ins for different membranes relative to the errors in calculated values of Δ ins .…”
Section: Insertion Barrier Depends On a Membrane's Interfacial Hydrop...mentioning
confidence: 99%
“…Similarly, Wang et al [27] studied mixed surfaces comprised of polar and non-polar regions of the melittin protein, and found that polar patches disproportionately suppress surface hydrophobicity (Figure 3g). Finally, Rego et al [30] classified protein regions according to their ease of dewetting, and found that hydrophobic and hydrophilic patches had remarkably similar chemical compositions, and contained comparable numbers of non-polar and polar atoms.…”
Section: Protein Hydrophobicitymentioning
confidence: 99%
“…The use of interfacial fluctuations to characterize the hydrophobicity of complex surfaces has highlighted that hydrophobicity can be remarkably sensitive to curvature and chemical patterning [20][21][22][23][24], and that approximate approaches for estimating hydrophobicity, based on surface area or additivity, are doomed to fail for all but the simplest of systems [25][26][27][28]. We then discuss how an understanding hydrophobic hydration and the ability to characterize hydrophobicity inform the thermodynamic forces that drive hydrophobic interactions and assemblies [29,30]. We also discuss how water density fluctuations in confinement between hydrophobic solutes can influence the kinetics and pathways of hydrophobic assembly [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Going from small solutes all the way up to large biomolecules, a subtle balance between hydrophilic and hydrophobic interactions is what dictates hydration free energies. [16][17][18][19][20][21][22][23][24] Evaluating such balance requires a local mapping of hydrophilic and hydrophobic contributions, which remains a challenge for both theory and experiments. 18,19,[25][26][27][28][29] From the experimental side, these contributions are notoriously difficult to probe and cannot be dissected by standard calorimetry approaches.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Evaluating such balance requires a local mapping of hydrophilic and hydrophobic contributions, which remains a challenge for both theory and experiments. 18,19,[25][26][27][28][29] From the experimental side, these contributions are notoriously difficult to probe and cannot be dissected by standard calorimetry approaches. Nevertheless, several attempts have been undertaken since the ability to characterize hydration thermodynamic properties would guarantee major economic advantages for e.g.…”
mentioning
confidence: 99%